Cytogenetic analysis of the South American fruit fly Anastrepha fraterculus (diptera:tephritidae) species complex : construction of detailed photographic polytene chromosome maps of the Argentinian af. sp.1 member - Gariou-Papalexiou, Aggeliki (2016)
Genetic and cytogenetic studies constitute a significant basis for understanding the biology of insect pests and the design and the construction of genetic tools for biological control strategies. Anastrepha fraterculus is an important pest of the Tephritidae family. It is distributed from southern Texas through eastern Mexico, Central America and South America causing significant crop damage and economic losses. Currently it is considered as a species complex; until now seven members have been described based on multidisciplinary approaches. Here we report the cytogenetic analysis of an Argentinian population characterized as Af. sp.1 member of the Anastrepha fraterculus species complex. The mitotic karyotype and the first detailed photographic maps of the salivary gland polytene chromosomes are presented. The mitotic metaphase complement consists of six (6) pairs of chromosomes, including one pair of heteromorphic sex chromosomes, with the male being the heterogametic sex. The analysis of the salivary gland polytene complement shows a total number of five long chromosomes that correspond to the five autosomes of the mitotic karyotype and a heterochromatic network corresponding to the sex chromosomes. Comparison of the polytene chromosome maps between this species and Anastrepha ludens shows significant similarity. The polytene maps presented here are suitable for cytogenetic studies that could shed light on the species limits within this species complex and support the development of genetic tools for sterile insect technique (SIT) applications.